Achieving simultaneous improvement of bendability and deep drawability of Al–Mg–Si alloy via intermediate annealing - Xin Zhan; Jianguo Tang; Xiaofen Tan; Mingan Chen; Wenhui Liu; Lingyong Cao; Lingying Ye; Xini Yuan; Gaohui Cao; Yong Zhang; Xiyan Hu; Xiaoguang Zhao (Journal of Materials Research and Technology)
This study explores the effects of intermediate annealing (IA) on the microstructure, texture, bendability, and deep drawability of an Al–Mg–Si alloy. It is found that that IA induces particle precipitation and static softening, leading to increases of the average size, number density, and volume fraction of both coarse and fine particles, along with a weakening of rolling texture. These effects become more pronounced with rising IA temperature. The changes in particle distribution and texture significantly influence the final grain size and texture, thereby affecting both bendability and deep drawability. The bendability of the IA-treated sheets is improved as the IA temperature increases, due to the changes in texture components from P and CubeND to Cube. Compared to the Non-IA sheet (dominated by Cube texture), the sheet treated with IA at 430 °C exhibits better bendability due to refined grain sizes. Introducing IA or increasing IA temperature improves the deep drawability by weakening the texture intensity of the T4P sheets. These results suggest that achieving both high bendability and deep drawability in Al–Mg–Si alloy is feasible by optimizing IA temperature. This study provides an experimental basis for the possibility of broader applications of Al–Mg–Si alloys in the automotive industry.